Metrics for software requirements specification quality quantification. (December 2021) - Ramesh, M.R. Raja; Reddy, Ch. Satyananda
Abstract: The initial and crucial phase of the automation and software development is identifying requirements and documenting them in an appropriate format that denotes software requirement specification (SRS). The quality and productivity at different phases of the software development depend on requirements specification. The quality of the end product of software development is proportionate to the quality of SRS. Hence, estimating the quality of the SRS is essential. Though the numerous metrics have been defined in contemporary research, the IEEE standard metrics are considered authentic to scale SRS quality. This manuscript endeavored to redefine the IEEE standard metrics' measuring approaches to improvise SRS quality assessment. The experimental study exhibiting the significance and robustness of the proposed approach that compared to the contemporary contributions of the recent literature